Determinasi Keterampilan dan Motivasi Teknologi terhadap Kreativitas Mahasiswa PGSD dalam Mendesain Worksheet Joyful learning - Zuhra Meiliza; Eli Meivawati; Husnul Khatimah (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
The advancement of digital technology requires pre-service teachers to possess both the skills and motivation to utilize technology. They should not be passive users but rather active developers of instructional media that incorporate technological elements. This study aims to analyze the influence of technological skills and technological motivation on students’ creativity in designing joyful learning-based worksheets. The research was conducted in July 2025, involving 118 students from the Elementary Teacher Education (PGSD) program at Universitas Sulawesi Barat. Data were collected using a four-point Likert scale questionnaire comprising 17 items, of which 8 were validated. Data analysis employed Structural Equation Modeling-Partial Least Squares (SEM-PLS) using SmartPLS software. Descriptive analysis revealed that the majority of respondents were 20 years old (53%) and predominantly female (82.2%). The measurement model (outer model) confirmed the validity and reliability of the instrument, while the structural model (inner model) yielded an R² value of 0.752 for the student creativity construct, indicating a strong effect. Bootstrapping analysis showed that both technological skills (p = 0.000) and technological motivation (p = 0.000) had a positive and significant influence on student creativity. These findings affirm that the higher the students’ technological skills and motivation, the greater their creativity in developing innovative instructional media. This study expands the theoretical understanding of the integration between technology and pedagogical creativity, and offers practical implications for curriculum development that responds to the demands of the digital era.